Re-instatement of Sorbus harrowiana (Rosaceae), based on morphometric analysis - Meng Li; Steven P. Sylvester; Zhang-Pei Wang; Yi-Da Pei; Xin-Fen Gao; Yuan Zhao; Wen-Qi Jiang (PhytoKeys, 2020)
Sorbus harrowiana (≡Pyrus harrowiana), previously considered a synonym of Sorbus insignis (≡Pyrus insignis) in the Flora of China, is re-instated here and shown to be distinct from S. insignis, based on morphometric analysis, coupled with herbarium and field investigation. We also present for the first-time full descriptions, distributional records and notes for S. harrowiana and S. insignis.